Civil society in the Chi River, Northeast Thailand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Social Policy and Social Work at Massey University, Auckland, New Zealand - Choopug Suttisa (Massey University, 2005)
The thesis 'Civil Society in the Chi River, Northeast Thailand', aims to answer the questions of what civil society means in the Northeast Thai village context, which factors make civil society proactive and how civil society is activated. Participatory action research (PAR) was carried out in two communities in the Chi River Basin to answer the inquiries. The research discusses the contexts of the Northeast Region and the two communities in the Chi River Basin. The people in this area are of the Thai-Laos ethnic group and hold particular beliefs in an amalgam of Buddhism and animism which creates cultural rituals that are different from other regions. The society is based on kinship ties. The economic situation has transformed from an agrarian society to a commercial agriculture society. Through the research process the new term of 'grounded civil society' was created. It means 'the sphere of an autonomous group of local people who actively participate in collective action to deal with their struggles and promote their common interests by mobilizing cultural and social capitals in consort with other people to productively solve their problems. Grounded civil society may include traditional forms of mutual assistance, and formal or informal social associations. It seeks to have a significant influence on public policy at any level'. The research found that grounded civil society was activated by both outside and inside factors. The outside factors included the negative effect of government development projects and the intervention of the participatory action research, which stimulated local people to engage in civil society. The inside factors activating civil society were the poor economic conditions of the villagers and the social capital existing in the communities. The social capital was built up around kinship ties and cultural capital, which generated the social values and norms of the local people. The research concluded with an analysis of the causal links between social capital and civil society claiming that social capital facilitated the creation of civil society. Further research possibilities are suggested.
Keywords: Community participation; Social capital; Customs and rituals, Thailand; Economic development; Fields of Research::370000 Studies in Human Society::370100 Sociology::370108 Rural Sociology